Psychostimulants and social behaviors - Cid-Jofré, Valeska; Bahamondes, Tamara; Zúñiga Correa, Agustina; Ahumada Arias, Ivalú; Reyes-Parada, Miguel; Renard, Georgina M. (Frontiers in Pharmacology, 2024)
Mounting evidence from animal models and human studies indicates that psychostimulants can significantly affect social behaviors. This is not surprising considering that the neural circuits underlying the regulation and expression of social behaviors are highly overlapped with those targeted by psychostimulants, which in most cases have strong rewarding and, consequently, addictive properties. In the present work, we provide an overview regarding the effects of illicit and prescription psychostimulants, such as cocaine, amphetamine-type stimulants, methylphenidate or modafinil, upon social behaviors such as social play, maternal behavior, aggression, pair bonding and social cognition and how psychostimulants in both animals and humans alter them. Finally, we discuss why these effects can vary depending on numerous variables such as the type of drug considered, acute versus long-term use, clinical versus recreational consumption, or the presence or absence of concomitant risk factors.